Hubungan Antara Kohesivitas Kelompok dengan Dukungan Sosial bagi Mahasiswa Perantau yang Aktif di Organisasi Orang Muda Katolik, Gereja X Yogyakarta - Maria Melinda Rahail; Indra Wahyudi; FX. Wahyu Widiantoro (Jurnal Psikologi, 2020)
Migrant students who active in Catholic Youth organizations will face tasks and conflicts in groups. Tasks whose purpose is a task prepared and agreed upon by the management of Catholic Youth. While conflicts usually occur between group members. These conflicts can hinder fulfilling the needs of individual students, namely social support. Therefore conflicts that occur between members must be resolved so individual students who active in the Catholic Youth organization can serve God and fulfill their needs in groups. This study uses quantitative research methods with data collection using scale. The subjects in this study were Catholic students who were active in the Catholic Youth organization of the X Church of Yogyakarta, aged 18-24 years old, and were not married. Data analysis techniques used by product moment correlation techniques from Pearson. Results: The results of the study indicate that the rxy correlation coefficient = 0.643 with p = 0,000 (p < 0.01). This means that there is a significant positive relationship between social support and group cohesiveness obtained by migrant students in the organization of Catholic youth in the X Church of Yogyakarta. The effective contribution of group cohesiveness to social support was 41.34% compared to other factors.Migrant students who active in Catholic Youth organizations will face tasks and conflicts in groups. Tasks whose purpose is a task prepared and agreed upon by the management of Catholic Youth. While conflicts usually occur between group members. These conflicts can hinder fulfilling the needs of individual students, namely social support. Therefore conflicts that occur between members must be resolved so individual students who active in the Catholic Youth organization can serve God and fulfill their needs in groups. This study uses quantitative research methods with data collection using scale. The subjects in this study were Catholic students who were active in the Catholic Youth organization of the X Church of Yogyakarta, aged 18-24 years old, and were not married. Data analysis techniques used by product moment correlation techniques from Pearson. Results: The results of the study indicate that the rxy correlation coefficient = 0.643 with p = 0,000 (p < 0.01). This means that there is a significant positive relationship between social support and group cohesiveness obtained by migrant students in the organization of Catholic youth in the X Church of Yogyakarta. The effective contribution of group cohesiveness to social support was 41.34% compared to other factors.